FAKTOR-FAKTOR YANG MENDORONG NEGARA-NEGARA ASIA PASIFIK DALAM MEMBENTUK KERJASAMA KOMPREHENSIF UNTUK MENCIPTAKAN STABILITAS KEAMANAN KAWASAN - Irawan Bayu Pratama (2013)
This article shown what's exactly becoming the encourage factors of the Asia Pacific states to create security stability in the region with a cooperative comprehensive. In order to implemented that, the region should be consider the function of comprehensive security, where the stability and cooperative could be shaped if all states combine and conceive security in two factors; traditional (military) and non-traditional (economy-politics). With the post-Cold War that change security in Asia Paci